2019
DOI: 10.3390/medicina55070399
|View full text |Cite
|
Sign up to set email alerts
|

Addition of 100 mg of Tramadol to 40 mL of 0.5% Ropivacaine for Interscalene Brachial Plexus Block Improves Postoperative Analgesia in Patients Undergoing Shoulder Surgeries as Compared to Ropivacaine Alone—A Randomized Controlled Study

Abstract: Background and objectives: Brachial plexus block is commonly used in shoulder surgery, as it provides satisfactory surgical conditions and adequate postoperative pain control. However, there are contradictory reports regarding the addition of tramadol to the injected regional anesthetic solution. We performed a prospective randomized study to evaluate the effectiveness of tramadol as an adjuvant to ropivacaine during interscalene brachial plexus block and assess its impact on the opioid consumption and the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Such varied results with local anesthetic adjuvants have been reported with other nerve blocks as well. Soulioti et al [ 34 ] in an RCT reported improved outcomes with the addition of 100 mg of tramadol to brachial plexus block with ropivacaine. In contrast, no such benefit was noted by Kesimci et al [ 35 ] using a similar dose of tramadol with ropivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…Such varied results with local anesthetic adjuvants have been reported with other nerve blocks as well. Soulioti et al [ 34 ] in an RCT reported improved outcomes with the addition of 100 mg of tramadol to brachial plexus block with ropivacaine. In contrast, no such benefit was noted by Kesimci et al [ 35 ] using a similar dose of tramadol with ropivacaine.…”
Section: Discussionmentioning
confidence: 99%
“…The Bruggrmann comfort scale (BCS) [ 13 ] was used to evaluate the comfort level of patients in the three groups, in which 0 points were considered as continuous pain, 1 point as no pain at rest and severe pain during deep breathing or coughing, 2 points as no pain when lying at rest and slight pain during deep breathing or coughing, 3 points as no pain during deep breathing, and 4 points as no pain during coughing.…”
Section: Methodsmentioning
confidence: 99%
“…Tramadol's effectiveness and safety as an adjuvant to LA for PNB are inconsistent (17,19,36,51). Several studies and systematic reviews have investigated tramadol as an adjuvant in BPB but often yielded contradictory results (52,79).…”
Section: Tramadolmentioning
confidence: 99%
“…Reviews by Koyyalamudi et al and Kirksey et al investigate tramadol with different local anesthetics (like bupivacaine, levobupivacaine, mepivacaine, and ropivacaine) in various PNBs (interscalene, axillary brachial plexus) reveal the often contradictory nature of the results (19,36). Recently, a 2019 RCT found that 100 mg tramadol with 0.5% ropivacaine for interscalene BPB lowered pain scores and cumulative morphine consumption 24h post-surgery (79). The authors claimed that the low incidence of complications suggests the safety of tramadol-ropivacaine combination to improve postoperative analgesia (79).…”
Section: Tramadolmentioning
confidence: 99%
See 1 more Smart Citation